Graphitization of carbon-based catalyst for improving the performance of negative electrode in vanadium redox flow battery. (21st April 2021) - Hou, Bingxue; Tang, Rui; Zhang, Qi; Cui, Xumei; Chen, Yungui
Abstract: Carbon-based materials were prepared to catalyze the V 3+ /V 2+ couple of vanadium redox flow battery using chitosan as the preliminary material and FeCl3 as activating agent. Graphite microcrystals were the main structures of the obtained catalyst (CTS-Fe-900) activated by FeCl3, and they contained a large number of curled and overlapped carbon nanosheets. Compared with CTS-D-900 (without FeCl3 as an activating agent), CTS-Fe-900 exhibits a better structure, higher graphitization degree, stronger current response, and smaller charge transfer resistance. The charge/discharge measurements indicates that the performances of the cell are improved by using the CTS-Fe-900-modified negative electrode in terms of increased discharge capacity and energy efficiency. Compared with pristine cell, the capacity retention for the CTS-Fe-900 modified cell maintains 82.2% at 50 mA cm −2 after 50 cycles, increased by 5.2%, and the corresponding energy efficiency reaches 81.3%, enhanced by 5.1%. This work reveals that CTS-Fe-900 catalyst can improve the comprehensive energy storage performance. The excellent electrocatalytic properties are mainly attribute to the effect of the FeCl3 template and the increase in the degree of graphitization.